THE ARTISTIC FORM OF RUSSIAN EPICS AND UZBEK DASTANS (COMPARATIVE ASPECT) (TAMADDUN NURI JURNALI, 2025)
The article is devoted to the analysis of Russian epics and Uzbek epics as specific genres of folk oral creativity, reflecting the cultural and historical characteristics of their people. The article also conducts a comparative analysis of the two genres, identifying common features and differences in their structure, poetics and narrative. In both genres, the emphasis is on heroic and moral values.